Exploring Self-Perceived Employability and Ambition of Student Veterans in a Higher Education Institution in the United States - Niu, Yuanlu; Zhu, Yidan; Xu, Xu; Hunter-Johnson, Yvonne (Journal of Interdisciplinary Studies in Education, 2022)
In this study, we explore the perceived employability and ambition of student veterans, compare the perceived employability and ambition of student veterans and civilian students, and examine the impact of other variables (e.g., age, gender, GPA, etc.) on student veterans’ perceived employability and ambition. An online survey was conducted among 85 students, including 37 veterans and 48 civilian students. The results show that most of the investigated student veterans were confident in their employability and future career success. In addition, student veterans had slightly lower perceived employability and ambition than either active military members or civilian students. The result of descriptive analysis showed clues that explained how other variables impacted the perceived employability and ambition of student veterans.